Prosthetic hip joint infection by Bacillus Calmette-Guerin therapy following intravesical instillation for bladder cancer identified using whole-genome sequencing: a case report - Riste, Michael; Davda, Pretin; Smith, E. Grace; Wyllie, David H.; Dedicoat, Martin; Jog, Simantini; Laird, Steven; Langman, Gerald; Jenkins, Neil; Stevenson, Jonathan; O’Shea, Matthew K. (BMC infectious diseases, 2021)
Background Joint replacement is an effective intervention and prosthetic joint infection (PJI) is one of the most serious complications of such surgery. Diagnosis of PJI is often complex and requires multiple modalities of investigation. We describe a rare cause of PJI which highlights these challenges and the role of whole-genome sequencing to achieve a rapid microbiological diagnosis to facilitate prompt and appropriate management. Case presentation A 79-year-old man developed chronic hip pain associated with a soft-tissue mass, fluid collection and sinus adjacent to his eight-year-old hip prosthesis. His symptoms started after intravesical Bacillus Calmette-Guerin (BCG) therapy for bladder cancer. Synovasure™ and 16S polymerase chain reaction (PCR) tests were negative, but culture of the periarticular mass and genome sequencing diagnosed BCG infection. He underwent a two-stage joint revision and a prolonged duration of antibiotic therapy which was curative. Conclusions BCG PJI after therapeutic exposure can have serious consequences, and awareness of this potential complication, identified from patient history, is essential. In addition, requesting appropriate testing is required, together with recognition that traditional diagnostics may be negative in non-pyogenic PJI. Advanced molecular techniques have a role to enhance the timely management of these infections.